DESIGNING PROMOTIONAL VIDEOS FOR ADIVASA RESIDENTIAL COMPLEX USING THE DESIGN THINKING - Romadhon, Alfian; Prameswari, Nadia Sigi (LPPM Univ. Ibn Khaldun Bogor, 2025)
The high dynamics of the Indonesian property market are influenced by a shift in consumer behavior towards digital media. In this context, Adivasa housing in Semarang presents a strong